Manoeuvring barriers: Assessing adaptive strategies for and persistent barriers to urban Nature-based Solutions in Lilongwe, Malawi - Bauer, Willi; Titz, Alexandra (Nature-Based Solutions, 2025)
Urban Nature-based Solutions (NbS) are increasingly promoted globally as a multifunctional and cost-effective way to address social and environmental challenges in cities. Based on these premises, there is a growing municipal interest in promoting NbS in cities of the so-called 'Global South'. However, current research is still clearly biased towards the 'Global North', with particularly few studies focusing on cities in Sub-Saharan Africa (SSA). As a result of these research gaps, there is a high risk that maladapted NbS – modelled on examples from other regions that do not meet local requirements and needs – will be adopted. Against this background, this article examines barriers to the adoption of urban Nature-based Solutions and the opportunities for successful implementation of NbS in cities in Malawi. Drawing on qualitative data (workshops, narrative expert interviews, group discussions) collected during five research stays in Lilongwe (2022–2024), the article outlines and analyses in detail the strategies employed to overcome these barriers by those actors in charge for implementing the Lilongwe Ecological Corridor Initiative (LECI), a large-scale NbS in the country's capital city. By empirically exploring the particularities of the implementation of the LECI, the article characterises features of NbS in SSA rarely explored in other contexts, such as the reframing of existing greenspaces, the pragmatic adaptation of NbS-plans and the formulation of by-laws as part of their planning. These insights can serve as a basis for further conceptual developments and critical engagement and to promote a deeper understanding of the potentials and pitfalls of implementation strategies seeking to manoeuvre persistent barriers.
CRIS-Team Scopus Importer:2025-03-14
Keywords: Adaptive strategies; Barriers; Lilongwe Ecological corridor initiative; Malawi; Nature-based Solutions; Urban greening

Reframing Urban Nature-Based Solutions Through Perspectives of Environmental Justice and Privilege - Bauer, Willi (Urban Planning, 2023)
Since its introduction, the concept of "nature-based solutions" has gained much attention, drawing public funds and private investments. Nature-based solutions conceptualise the use of nature in planning as a cost-efficient and sustainable means to address societal, economic, and ecological challenges. However, this "triple win" premise tends to conceal potentially resulting injustices, such as displacement through green gentrification. While these injustices have attracted the atten-tion of environmental justice scholars, as exemplified by the "just green enough" approach, links to the "nature-based solutions" concept are mostly implicit. Further, the concept of environmental privilege, questioning who benefits from created natural amenities, has rarely been taken up. This article, therefore, argues that environmental justice should be linked closely to nature-based solutions. Supported by a theoretical perspective, the article aims at exploring who benefits from, and who loses out on, urban nature-based solutions processes. It builds on a qualitative literature review of the schol-arly landscape on environmental justice and urban greening while linking to nature-based solutions, adding perspectives of environmental privilege. In this, it attempts to offer three important contributions to the current academic discussion. First, the article provides an overview of the debate on urban greening, (in)justice, and environmental privilege. Second, it relates the concept of nature-based solutions to the debate on environmental justice, opening nature-based solutions up for critique and conceptual refinements. Third, it outlines a way forward for reframing nature-based solutions through the lens of environmental justice and privilege. Thus, this article provides a starting point for further discussions on the implementation of just nature-based solutions in cities.
CRIS-Team WoS Importer:2023-04-21

Tracing the urbanisation of risk in Malawi: A multilevel analysis - Bauer, Willi; Titz, Alexandra; Manda, Mtafu C. (Jàmbá, 2024)
Cities in Malawi have long been outside the focus of disaster risk reduction. As a result, urban risks remain poorly understood, and urban governments and disaster risk reduction (DRR) practitioners working in cities struggle to adequately support vulnerable urban populations. This is evidenced by recent disasters such as Cyclone Freddy, which devastated the city of Blantyre in 2023, and increasingly common small-scale events in urban areas. This article analyses the Malawian city as a distinct riskscape, shaped by national-level policies of neglect that create an institutional void that DRR practitioners working at the city level struggle to fill. This process is complicated by a multitude of challenges at different levels of governance, especially leaving small-scale events prevalent in urban areas largely unaddressed. This process of risk accumulation is increasingly affecting urban residents. Methodologically, we demonstrate this through a comprehensive policy analysis and by drawing on expert and civil society interviews and questionnaires conducted in Lilongwe City. Contribution: By outlining the interlocking challenges at multiple levels and grounding them in empirical data, we highlight the specificities of urban DRR efforts in Malawi and provide opportunities to improve them.
CRIS-Team Scopus Importer:2024-09-20
Keywords: disaster risk reduction; global south; governance; Malawi; multilevel analysis; urban vulnerability